2021
DOI: 10.1101/2021.06.09.447716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alzheimer’s disease BIN1 coding variants increase intracellular Aβ by interfering with BACE1 recycling

Abstract: Genetics identified BIN1 as the second most important risk locus associated with late-onset Alzheimer's disease after APOE4. Here we show the consequences of two coding variants in BIN1 (rs754834233 and rs138047593), both in terms of intracellular beta-amyloid accumulation (iAbeta) and early endosome enlargement, two interrelated early cytopathological Alzheimer's disease phenotypes, supporting their association with LOAD risk. We previously found that Bin1 deficiency potentiates beta-amyloid production by dec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…Moreover, it has been also shown that BIN1 depletion impacts BACE1 trafficking, causing its endosomal accumulation and, consequently, favoring Aβ production (Ubelmann et al, 2017). In line with this evidence, rare coding variants including rs754834233 or rs138047593 impact on AD risk reducing BACE1 recycling and causing early endosome enlargement recapitulating the same phenotype of Bin1 knockdown (Perdigão et al, 2021;. Beside this, BIN1 expression correlates also with tau pathology (Calafate et al, 2016), indeed it directly interacts with tau and such interaction is downregulated by tau phosphorylation on Thr231 (Sottejeau et al, 2015).…”
Section: Bin1supporting
confidence: 53%
“…Moreover, it has been also shown that BIN1 depletion impacts BACE1 trafficking, causing its endosomal accumulation and, consequently, favoring Aβ production (Ubelmann et al, 2017). In line with this evidence, rare coding variants including rs754834233 or rs138047593 impact on AD risk reducing BACE1 recycling and causing early endosome enlargement recapitulating the same phenotype of Bin1 knockdown (Perdigão et al, 2021;. Beside this, BIN1 expression correlates also with tau pathology (Calafate et al, 2016), indeed it directly interacts with tau and such interaction is downregulated by tau phosphorylation on Thr231 (Sottejeau et al, 2015).…”
Section: Bin1supporting
confidence: 53%